Model Persamaan Simultan pada Analisis Hubungan Kemiskian dan PDRB - Bekti, Rokhana Dwi; David, David; N, Gita; Priscillia, Priscillia; Serlyana, Serlyana (Bina Nusantara University, 2014)
Simultaneous model is a model for some equation which have simultaneous relationships. It was often found in econometrics, such as the relationship between Gross Domestic Regional Product (GDRP) and poverty. GDP is a common indicator that can be used to determine the economic growth occurred in region. Meanwhile, poverty is one of the indicators to measure the society welfare. Information about these relathionships were important to perform the relathionsips between GDP and poverty. So this research conducted an analysis to obtain simultaneous models between GDRP and poverty. Estimation of the parameters used is Two-Stage Least Squares Estimation (2SLS). The data used are 33 provinces in Indonesia at 2010. By α = 5%, it was conclude that variable which significant effect on GDRP is poverty, export, and import. Meanwhile, the variables that significantly affect poverty are population. The simultaneous model (α = 5%) also conclude that there is no simultaneous relationship between GDRP and poverty. However, with α = 25%, there is a simultaneous relationship between GDRP and poverty.